Determinants of Entrepreneurial Behaviour of Vegetable Growers - Shailesh Kumar , Gyanendra Sharma , K. Srinivas and V. K. Yadav, (Indian Journal of Extension Education, 2013)
The present study was conducted in Uttarakhand state to find out the components of entrepreneurial behaviour ofvegetable growers. For this purpose, a sample of 120 vegetable growers through multi-stage sampling technique wasselected. It was found that achievement motivation (0.782), self confidence (0.782), management orientation (0.744),leadership ability (0.559) and farm decision making (0.525) were higher factors loading to influence the entrepreneurialbehaviour. Second levels of influential variables were innovativeness (0.665) and knowledge of vegetable cultivation(0.569). The findings indicate that management orientation, farm decision making, leadership ability, achievementmotivation and self confidence are crucial for affecting entrepreneurial behaviour of vegetable growers. Findings of thestudy are helpful in selecting appropriate motivational training for the hill farmers particularly